Efforts to conserve endangered terrestrial orchids in situ and ex situ at two natural reserves within Central Mexico - Rangel-Villafranco, Mónica (Universidad de Costa Rica, 2015)
The natural vegetation in and around Mexico City once harbored an unusually high number of plant and animal (insect) species, including endemics (Vázquez 1973, Ceballos & Galindo 1984, Rzedowski 1991). The high diversity in this region has been attributed to the unusual topography resulting from a series of volcanic eruptions that ended ca. 1800 years ago (Siebe et al. 2004). In addition, two phyto-geographic regions overlap within Central Mexico that support diverse vegetation types (e.g., shrubs, mature pine forests).